2013
DOI: 10.1590/s1676-06032013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Structure and floristic relationships between Cerrado sensu stricto sites on two types of substrate in northern Cerrado, Brazil

Abstract: Structure and floristic relationships between Cerrado sensu stricto sites on two types of substrate in northern Cerrado, Brazil. Biota Neotrop. (13)4: http://www.biotaneotropica.org.br/v13n4/en/abstract?article+bn02213042013 Abstract: We described and compared the floristic composition, richness, species diversity and structure of the tree-shrub component in pairs of Typical Cerrado (Cerrado Típico) and rocky outcrop Cerrado (Cerrado Rupestre) in two localities in Tocantins State. In each locality, we set up 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
2
18
0
3
Order By: Relevance
“…Abreu et al (2012) and Mews et al (2014) suggested-but did not test their hypothesis-that the considerable environmental heterogeneity of the RS is the main factor promoting species diversity in this environment, despite the lower density of plants found in this environment, and the physical limitations imposed by the rocky outcrops (Pinto et al 2009;Abreu et al 2012;Mews et al 2014), these environments were similar in their species diversity. A number of previous studies (e.g., Gomes et al 2011;Maracahipes et al 2011;Abreu et al 2012;Lemos et al 2013;Mews et al 2014) also recorded similarities in the diversity of woody plant species in Cerrado savanna vegetation growing on different types of substrate, which indicates that this parameter may not be affected directly by the depth of the substrate or the chemical and granulometric properties of the surface layers of the soil. We confirmed here that the limitations of the RS substrate are counterbalanced by the greater heterogeneity of microsites found in this environment (measured here in terms of the variation in the chemical and granulometric properties of the soil), which support the occurrence of a variety of species, resulting in the similarities in species richness and diversity found between the RS and DS.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Abreu et al (2012) and Mews et al (2014) suggested-but did not test their hypothesis-that the considerable environmental heterogeneity of the RS is the main factor promoting species diversity in this environment, despite the lower density of plants found in this environment, and the physical limitations imposed by the rocky outcrops (Pinto et al 2009;Abreu et al 2012;Mews et al 2014), these environments were similar in their species diversity. A number of previous studies (e.g., Gomes et al 2011;Maracahipes et al 2011;Abreu et al 2012;Lemos et al 2013;Mews et al 2014) also recorded similarities in the diversity of woody plant species in Cerrado savanna vegetation growing on different types of substrate, which indicates that this parameter may not be affected directly by the depth of the substrate or the chemical and granulometric properties of the surface layers of the soil. We confirmed here that the limitations of the RS substrate are counterbalanced by the greater heterogeneity of microsites found in this environment (measured here in terms of the variation in the chemical and granulometric properties of the soil), which support the occurrence of a variety of species, resulting in the similarities in species richness and diversity found between the RS and DS.…”
Section: Discussionmentioning
confidence: 72%
“…Despite these differences in species composition and vegetation structure, studies of adjacent RS and DS savannas have found little variation in the species diversity of the RS and DS (Gomes et al 2011;Maracahipes et al 2011;Abreu et al 2012;Lemos et al 2013;Mews et al 2014). Mews et al (2016) concluded that the marked differences between the substrates of these two environments are responsible for the differences in the composition of their plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…(n = 14). Despite high beta-diversity in the Cerrado biome, a few dominant species (oligarchic species) often account for most of the total denisity in many physiognomies [ 39 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…(Mid-west Brazil). Lemos et al (2013), in similar studies in a Cerrado sensu stricto area in Tocantins state (Mid-west Brazil) suggest that A. occidentale and Q. parviflora seem not to be influenced by different kinds of substrates. Ratter et al (2003) point that taxa of the genus Qualea are well-adapted to different substrates, and thus are widely distributed by the Cerrado biome.…”
Section: Physical/chemical Aspects Of the Soilmentioning
confidence: 67%